Growth and development of Conyza bonariensis based on days or thermal units - Soares, Daniel Jorge; Oliveira, Wladecir Salles de; Uzuele, Elvio Lorençato; Carvalho, Saul Jorge Pinto de; López-Ovejero, Ramiro Fernando; Christoffoleti, Pedro Jacob (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate the growth and development of a glyphosate-resistant population of Conyza bonariensis in different sowing dates (autumn, winter, and spring) and in two agricultural environments, based on days or thermal units. Five experiments were performed in two agricultural environments in Brazil: two in the municipality of Não-Me-Toque, in the state of Rio Grande do Sul – with sowings in July and September 2011; and three in the municipality of Santa Cruz das Palmeiras, in the state of São Paulo ‒ with sowings in April, July, and September 2011. In each trial, ten evaluations of the phenological development and total dry mass of C. bonariensis were performed, fitting these variables to a unit of time in days or growing degree days. The phenological development of C. bonariensis had the best adjustment at the base temperature of 8.4°C, and was affected by sowing date and agricultural environment. In autumn, with decreasing temperature and photoperiod, plants are still able to accumulate dry mass, but without floral induction. In spring, with increasing temperature and photoperiod, dry mass accumulation is lower, but phenological development is faster, with significant floral induction.